Reviews of Environmental Contamination and Toxicology volume With Cumulative and Comprehensive Index Subjects Covered Volumes 221-230 - Whitacre, David M.; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2014)
CONTENTS Foreword Preface Removal of Vapor-Phase Elemental Mercury from Stack Emissions with Sulfur-Impregnated Activated Carbon Mohammad Hossein Sowlat, Mohammad Abdollahi, Hamed Gharibi, Masud Yunesian, and Noushin Rastkari Setting Water Quality Criteria in China: Approaches for Developing Species Sensitivity Distributions for Metals and Metalloids Yuedan Liu, Fengchang Wu, Yunsong Mu, Chenglian Feng, Yixiang Fang, Lulu Chen, and John P. Giesy Toxicity Reference Values for Protecting Aquatic Birds in China from the Effects of Polychlorinated Biphenyls Hailei Su, Fengchang Wu, Ruiqing Zhang, Xiaoli Zhao, Yunsong Mu, Chenglian Feng and John P. Giesy Fabricated Nanoparticles: Current Status and Potential Phytotoxic Threats Tushar Yadav, Alka A. Mungray, Arvind K. Mungray Status of Heavy Metal Residues in Fish Species of Pakistan Majid Hussain, Said Muhammad, Riffat N. Malik, and Muhammad U. Khan Cumulative and Comprehensive Index (Volumes 221-230).
Removal of Vapor-Phase Elemental Mercury from Stack Emissions with Sulfer-Impregnated Activated Carbon -- Setting Water Quality in China: Approaches for Developing Species Sensitivity Distributions for Metals and Metalloids -- Toxicity Reference Values for Protecting Aquatic Birds in China from the Effects of Polychlorinated Biphenyls -- Fabricated Nanoparticles: Current Status and Potential Phytotoxic Threats -- Status of Heavy Metal Residues in Fish Species of Pakistan -- Cumulative Index.
Keywords: Ecotoxicology; Environmental management; Waste management; Ecotoxicology; Environmental Management; Waste Management/Waste Technology